The effects of soybean hulls and their particle size on growth performance and carcass characteristics of finishing pigs - D L Goehring; Joel M DeRouchey; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2012)
A total of 1,235 pigs (PIC 337 × 1050; initially 68.4 lb) were used in a 118-d study to determine the effects of 7.5 and 15% ground or unground soybean hulls on growth performance and carcass characteristics of finishing pigs raised in a commercial environment. Pens of pigs were balanced by initial weight and randomly allotted to 1 of 5 dietary treatments in a completely randomized design with 26 to 28 pigs per pen and 9 replications per treatment. Treatments were arranged in a 2 × 2 factorial, and main effects were soybean hull particle size (unground or ground, 787 and 370 Î¼, respectively) and amount of soybean hulls (7.5 or 15%) in corn-soybean meal—based diets. The fifth treatment was a positive control, a corn-soybean meal—based diet. No particle size × soybean hull interactions (P>0.18) occurred. Overall (d 0 to 118), increasing soybean hulls, regardless of particle size, did not affect ADG but numerically increased (P = 0.11) ADFI, resulting in poorer (linear, P<0.02) F/G. Although F/G became worse, increasing soybean hulls in the diet improved (linear, P<0.002) caloric efficiency on an ME and NE basis, indicating that published energy values undervalue the energy content of soybean hulls. Unexpectedly, grinding soybean hulls to a lower particle size worsened F/G (P<0.04) and caloric efficiencies (P<0.03).; Swine Day, Manhattan, KS, November 15, 2012
Keywords: Kansas Agricultural Experiment Station contribution; no. 13-026-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1074; Swine; Finishing pig; Particle size; Soybean hulls